Graphic subjects : critical essays on autobiography and graphic novels - Chaney, Michael A. (Wisconsin Studies in Autobiography, 2011)
Some of the most noteworthy graphic novels and comic books of recent years have been entirely autobiographical. In Graphic Subjects , Michael A. Chaney brings together a lively mix of scholars to examine the use of autobiography within graphic novels, including such critically acclaimed examples as Art Spiegelman’s Maus , David Beauchard’s Epileptic , Marjane Satrapi’s Persepolis , Alan Moore’s Watchmen , and Gene Yang’s American Born Chinese .             These essays, accompanied by visual examples, illuminate the new horizons that illustrated autobiographical narrative creates. The volume insightfully highlights the ways that graphic novelists and literary cartoonists have incorporated history, experience, and life stories into their work. The result is a challenging and innovative collection that reveals the combined power of autobiography and the graphic novel.